Antibacterial Additive for Polystyrene Based on Silver Nanoparticles Supported on Titanium Dioxide - Miguel A. Waldo-Mendoza; Lucía Martínez-Jothar; Socorro Oros-Ruiz; E. G. Villabona-Leal; Luis Manuel Céspedes-Covarrubias; Zoe V. Quiñones-Jurado; Eduardo Ortega; Elías Pérez (International Journal of Polymer Science)
Silver nanoparticles supported on titanium dioxide nanoparticles (Ag/TiO2) were incorporated and evaluated as antibacterial additive for polystyrene materials. These particles were synthesized using a deposition-precipitation method by adding silver nitrate as metallic precursor, sodium hydroxide as reducing agent, and commercial TiO2 (P25) as support. Rectangular pieces of polystyrene (PS) containing 100, 300, 500, and 700 ppm (wt.%) of the additive were made using an extrusion-injection molding process, and they were evaluated for their antibacterial properties against Escherichia coli using the Pour Plate method. Particles were distributed on the PS surface, and PS pieces presented a good antibacterial efficiency at 100, 300, and 500 ppm and decreased for 700 ppm due to an additive agglomeration on the PS surface. These results validate the antibacterial properties of Ag/TiO2, determine a concentration limit at which the additive is well distributed on the PS surface, and assess the importance of Ag in this system.